Ultrasonic high frequency guided wave for detection and identification of defect location in seal welds of sodium cooled fast reactor fuel subassemblies. (November 2019) - Dhayalan, R.; Kumar, Anish; Rajkumar, K.V.; Mukhopadhyay, C.K.
Highlights: Ultrasonic HFGW is used for defect detection in fuel subassembly hexcan seal weld. 2D FE models are developed to study the characteristics of HFGW in hexcan sheath. HFGW is able to detect 10% WT (320 µm) defect on both sides of the seal weld. Asymmetric displacement of HFGW led to different sensitivities for ID & OD defects. Time-Frequency analysis is used to identify the through thickness defect location. Abstract: Hexcan seal welds in fuel subassemblies of prototype fast breeder reactor (PFBR) pose serious problem during ultrasonic inspection for defects due to lower thickness involved and its complex structure. This paper presents detection of defects and identification of its localization across the thickness in fuel subassembly hexcan seal welds using high frequency guided (plate) waves (HFGW). The generation and propagation characteristic of the optimized guided wave mode is extensively studied by using 2D finite element method (FEM). The energy transfer between the hexcan sheath surfaces results in a better sensitivity for detection of small defects on both surfaces. The study demonstrates that the through-thickness location of the defects can be accurately determined by using the frequency content rather than time-of-flight information.